2022
DOI: 10.1021/acsami.2c16305
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species- and Cell-Free DNA-Scavenging Mn3O4 Nanozymes for Acute Kidney Injury Therapy

Abstract: Reactive oxygen species (ROS) scavenging therapy toward acute kidney injury (AKI) is promising, but no effective ROS scavenging drug has been developed yet. Moreover, cell-free DNA (cfDNA) is also involved in AKI, but the corresponding therapies have not been well developed. To tackle these challenges, Mn 3 O 4 nanoflowers (Nfs) possessing both ROS and cfDNA scavenging activities were developed for better AKI protection as follows. First, Mn 3 O 4 Nfs could protect HK2 cells through cascade ROS scavenging (dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 77 publications
0
20
0
Order By: Relevance
“…Several other substances that were traditionally known to act as antioxidants have been loaded into nanoparticles targeted to RTEC, successfully reducing oxidative stress in the injured kidney and mitigating kidney dysfunction [20 ▪ –26 ▪ ]. A promising strategy has been to co-load within nanocarriers both ROS scavengers along with drugs used to treat other damage mechanisms to further reduce inflammation [27 ▪▪ ] or intracellular calcium, which is believed itself to trigger multiple damage mechanisms [28 ▪▪ ].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Several other substances that were traditionally known to act as antioxidants have been loaded into nanoparticles targeted to RTEC, successfully reducing oxidative stress in the injured kidney and mitigating kidney dysfunction [20 ▪ –26 ▪ ]. A promising strategy has been to co-load within nanocarriers both ROS scavengers along with drugs used to treat other damage mechanisms to further reduce inflammation [27 ▪▪ ] or intracellular calcium, which is believed itself to trigger multiple damage mechanisms [28 ▪▪ ].…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Renal inflammation plays a notorious role in AKI, although systemic treatment with anti-inflammatory medications can present multiple adverse effects that limit their utility. To address this issue, the co-loading of kidney-specific anti-inflammatory agents into nanocarriers together with therapeutics for an additional injury mechanism has been attempted to better mitigate AKI [26 ▪ ,27 ▪▪ ,31 ▪ ,32 ▪ ]. For example, chemokine receptor 4 (CXCR4) is highly expressed in injured RTEC and enhances leukocyte recruitment during AKI.…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…The nanozyme inhibits O 2 and glucose deprivation‐mediated apoptosis, and endoplasmic reticulum stress, and provides robust neuroprotection against ischemic stroke and reperfusion (I/R) injury of brain tissue (Figure 8). [93] The Mn 3 O 4 nanoflowers with ROS scavenging and cell‐free DNA absorbing properties provide effective protection to the in vivo murine model against cisplatin‐induced and ischemia‐reperfusion acute kidney injury [94] …”
Section: Antioxidant and Prooxidant Nanozymesmentioning
confidence: 99%
“… 59 60 61 Thus, MNPs have both drug-carrying and self-therapeutic efficacy for treating various inflammatory diseases ( Table 1 ). 45 59 60 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 In this review, we discuss the roles of recently reported MNPs in the scavenging of reactive oxygen species (ROS) and in anti-inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%